Inventory Model for Order Quantity Optimization with Partial Backlogging on Greater Demand at The Beginning - Aritonang, Reanty Teresa; Darnius, Open; Sutarman, Sutarman (Politeknik Ganesha Medan, 2023)
This article discusses the model of inventory with greater demand at the beginning which allows shortages. During the shortage period, it is assumed that there is a backlogged demand, and the remainder is considered lost sales. This research is completed by using the deterministic inventory model method, namely the EOQ model. The result of using the EOQ method is to determine the inventory lot size and length, with the goal of minimizing the total cost of inventory and generating maximum profits related to the inventory model. An numerical example is given to show the use of this model.